Association of House Dust Allergen Concentrations With Residential Conditions in City and in Rural Houses - Aleksandra Wardzyńska, MD; Barbara Majkowska-Wojciechowska, MSc, PhD; Jolanta Pełka, MD; Leszek Korzon, MD; Magdalena Kaczała, MD; Marzanna Jarzębska, MSc; Tomasz Gwardys, MD; Marek L Kowalski, MD, PhD (World Allergy Organization Journal, 2012)
Background The aim of the study was to evaluate the relationship between house dust mite, cat and dog allergen levels with household characteristics in the houses of children living in urban and rural areas in central Poland.Methods Dust samples were collected from 141 urban and 191 rural houses. Der f1 + Der p1, Can f 1, and Fel d1 levels were measured and associated with residential conditions and atopy-related health outcomes assessed by clinical examination and skin prick testing.Results Concentrations of mite allergens were lower, and cat and dog allergen levels were higher in urban houses. Fel d1 and Can f1 levels depended on the presence of a respective animal in the house. In urban houses, Der p1 + Der f1 concentration was lower in households with central heating, whereas Can f1 concentration was related to building age. Multivariate analyses revealed that the concentrations of house dust mite and dog allergens were associated with relative humidity, number of people in the household, and the presence of a dog at home. There was no significant association between allergen level and sensitization or atopic diseases.Conclusions Concentrations of indoor allergens in urban and rural houses differ significantly, and residential conditions associated with allergen levels seem to be different in both environments. Keywords: allergen concentration, house dust mite, cat allergen, dog allergen, allergy, residential conditions